Application of soy protein isolate fiber and soy soluble polysaccharide non-covalent complex: A potential way for pH-triggered release. (15th February 2023) - Zhao, Hekai; Wang, Shengnan; Liu, Xiulin; Zhao, Guilan; Yang, Lina; Song, Hong; Zhang, Guangchen; He, Yutang; Liu, He
Graphical abstract: Highlights: SPIF/SSPS complex is stable at pH 2.0 and 4.0 and dissociated above pH 6.0. The original SPIF/SSPS complex emulsion possessed uniform and stable droplets. SPIF/SSPS complex emulsion showed pH-responsive stability. The curcumin in emulsion released slowly at pH 2.0 and 4.0, and rapidly above pH 6.0. Abstract: The non-covalent interactions between protein and polysaccharide have the potential to design responsive materials. In this study, soy protein isolate fiber/soy soluble polysaccharide (SPIF/SSPS) non-covalent complex was used to create an emulsion, and the pH–response performance was evaluated by investigating their microstructure, interfacial properties, and stability at pH values of 2.0–10.0. The SPIF/SSPS complex was relatively stable at pH 2.0 and 4.0, and the corresponding emulsions had uniform droplets that showed outstanding storage stability after 21 days. However, the SPIF/SSPS complex was dissociated gradually with the elevation of pH, especially under alkaline condition, that caused the flocculation and coalescence in emulsion. This phenomenon not only relate to electrostatic repulsion, but also relate to the disintegration of SPIF. Furthermore, the encapsulated curcumin is released rapidly from emulsion when the pH increased above 6.0. This research may provide an outstanding pH-response strategy that have the potential for pH-triggered release.